1992
DOI: 10.1007/bf00219172
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletions in interval 6 of the Y chromosome of males with idiopathic sterility point to disruption of AZF, a human spermatogenesis gene

Abstract: For males with idiopathic sterility, a molecular screen specific for small lesions (microdeletions) in interval 6 of the Y chromosome was set up using 29 Y-DNA probes. A "de novo" microdeletion in Y interval 6 was detected in 2 out of 19 "chromosomally normal" sterile males. The first microdeletion includes the Y-DNA probes pY6HP35 and 12f3; the second microdeletion includes the Y-DNA probes pY6HP52, 49f, FR15-II and the subinterval "C" of probe 50f2. A probe of the pY6H sequence family is present in both dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(74 citation statements)
references
References 22 publications
1
67
0
6
Order By: Relevance
“…In 1976, Tiepolo and Zuffardi first reported, from microscopic analysis of the Y chromosome in infertile men, that the human Y chromosome played a crucial role in spermatogenesis (Tiepolo and Zuffardi 1976). Since their identification of deletions of the long arm of the Y chromosome in infertile men, the existence of a spermatogenesis gene or azoospermic factor (AZF) on the Y chromosome has been proposed (Vogt et al 1992), and many investigators have focused on where genes related to spermatogenesis exist in the long arm of Y chromosome (Andersson et al 1988;Johnson et al 1989;Vogt et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1976, Tiepolo and Zuffardi first reported, from microscopic analysis of the Y chromosome in infertile men, that the human Y chromosome played a crucial role in spermatogenesis (Tiepolo and Zuffardi 1976). Since their identification of deletions of the long arm of the Y chromosome in infertile men, the existence of a spermatogenesis gene or azoospermic factor (AZF) on the Y chromosome has been proposed (Vogt et al 1992), and many investigators have focused on where genes related to spermatogenesis exist in the long arm of Y chromosome (Andersson et al 1988;Johnson et al 1989;Vogt et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify genes involving spermatogenesis, several researchers have analyzed the Y chromosome by various methods, such as Southern blot analysis and polymerase chain reaction (PCR) (Johnson et al 1989;Vogt et al 1992). In 1993, Ma et al reported two cDNAs of a Yspecific gene family named the RNA binding motif (RBM) from a region on the long arm of the Y chromosome that was deleted in some infertile patients (Ma et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These maps were based on the distinct location of Y-specific DNA probes selected from different Y chromosome clone libraries and the analyses of their presence or absence on DNA blots of a series of genomic DNA samples extracted from infertile men with microscopically visible Yq11 deletions and rearrangements [4][5][6] . On this molecular level, for the first time, we observed some interstitial microdeletions in Yq11 when screening azoospermic men with a normal-looking Y chromosome and a normal 46,XY karyotype [7,8] . At that time, interstitial microdeletions were already found in comparable dynamic chromosome regions of different autosomes [9] .…”
mentioning
confidence: 74%
“…In those males who have spermatogenetic failure, abnormalities of azoospermia factor genes in the euchromatic region on the long arm of the Y chromosome (Yq) have been reported [24] . The Yqmicrodeletions of azoospermia factor (AZF) regions are major causes of infertility associated with severe oligospermia and azoospermia [26] and may also be associated with somatic and germinal gonosomal mosaicism [27]- [29] . In males Y q+ may carry the increased risk of abortion as reported by Patil (1977) and Nielson (1978).…”
Section: Discussionmentioning
confidence: 99%